KARAKTERISTIK DAN AKAR MASALAH KEMISKINAN Kasus Pada 4 Tipologi Desa di Kabupaten Sumbawa - Iskandar, Syaifuddin; Mahmud, Amir; Muslim, Muslim (Universitas Muhammdaiyah Surakarta, 2010)
This research meant to dig and comprehends indicators distinguishing characteristic and poorness problem root in Sumbawa regency. Because of research region broadness, hence research subject is determined in purposive by four countrysides assessed representation able to in geographical typology complete and characteristic countryside public and also level of poorness of resident Sumbawa regency in general. As for fourth of countryside typology is rural area, mountain area, coastal area, and sub urban area. Analyzer applied to comprehend characteristic and poorness problem root of the countryside public, that is using analysis Method Participative Poorness, which developed with method Root Cause Analysis (RCA). This method applied to comprehend characteristic and poorness problem root in each countryside typology. The result of data analysis in general inferential that the poorness characteristic in each countryside typology actually not solely determined by region typology, because at most all countryside typologies there is poor resident amounts which relative still big. This condition altogether determined by economic indicators as factor that is very influences level of prosperity/ poorness of countryside public.